#TITLE_ALTERNATIVE# - TRIANA PAKPAHAN (NIM : 20911003)Pembimbing : Rukman Hertadi, D.Sc, MEIDY
Halophilic proteins have thrived to maximize stability and activity at a high salt concentrations. Understanding the haloadaptation mechanism particularly the influence of salt on function, folding and solubility is important, for it has obvious potential application in the biotechnological industry. We explore the properties of halophilic proteins through their primary, secondary and tertiary structure analysis. At primary level, we compare the amino acid composition of halophilic and their homologous nonhalophilic. The compositions of helix, sheet and coil formation are assessed in the secondary structure analysis. We also calculate the composition of polar and non-polar residues, solvent accessible surface area, number of saltbridges and radius of gyration to give us more information insight from the protein properties from tertiary structure. In addition, we perform systematic comparison between mesophilic and halophilic proteins regarding the content of various types of amino acid clusters. A spectral graph theory is employed to detect such clusters in the protein. As a result, we found that halophilic proteins are characterized with the lower propensities of Cys, over representation of helix and beta sheets, and their electrostatic core surface is more accessible by the solvent than their hydrophobic core surface. From the amino acid clusters analysis, we found that in average, the number of clusters in mesophilic shows a larger value than halophilic proteins. Nevertheless, despite the number of clusters is less than in mesophilic, halophilic proteins show majority of hydrophobic residues forming cluster in their proteins and aromatic residues, in particular for the high overlap aromatic clusters. This indicates that hydrophobic and aromatic cores of halophilic proteins are more vigorous, particularly residues with high interaction, and hence, have role in haloadaptation.